Robust ethical realism, necessary truths and the miracle of morality - Rafael Graebin Vogelmann (Ethic@: an International Journal for Moral Philosophy, 2023)
Non-naturalists about the normative face the problem of providing a metaphysical explanation for the supervenience of the normative on the natural. Recently, Gideon Rosen has argued that non-naturalists can side-step this problem by rejecting strong supervenience and the view that normative truths are metaphysically necessary. Rosen proposes to take normative truths to be normatively necessary, where normative necessity is different from and irreducible to metaphysical necessity. I argue that if Rosen is right, that creates a deeper problem for robust ethical realism (the view that there are mind-independent, non-natural moral facts). According to robust ethical realism, it is a normative fact that persons are an especially valuable kind of being. But if Rosen is right, that is a metaphysically contingent fact. The existence of persons is also contingent. According to robust ethical realism, then, there is a striking match between what the normative facts happen to be and the kinds of beings that happen to exist. Persons could have failed to exist and they could have failed to be valuable, but it just so happens to be a fact about the natural world that they exist and a normative fact that they have value. Given that this match is accidental, it amounts to a miraculous coincidence. To the extent that commitment to unexplained coincidences counts against a view, robust ethical realism faces a problem.